Innovation of Marketing Media through the Creative Digital Brochure with Local Wisdom - Wiradharma, Gunawan; Arisanty, Melisa; Riady, Yasir; Anam, Khaerul; Adamy, Zulham (Jurnal Komunikasi, 2022)
This article discusses marketing strategies related to the services of prospective millennial students through creative digital brochures based on local wisdom for Universitas Terbuka, Indonesia. The content in the existing printed brochure does not match the characteristics of millennial students and does not yet display the locality. As a solution, digital brochures can be a new medium for presenting products offered by universities as a cutting-edge innovation. Therefore, this research was conducted to design a creative digital brochure that contains local wisdom. In-depth interviews with prospective millennial students and the marketing team were conducted to obtain appropriate design input. Comprehensive results were obtained through this research which included components, the procedure, and design of creative digital brochures that are more attractive, and persuasive, and have the potential to increase the interest of the millennial generation in choosing Universitas Terbuka. The presence of this creative digital brochure can be an alternative branding tool to persuade the wider community, especially the millennial generation who are one of the main target markets.